Penguatan kewarganegaraan ekologis melalui pemberdayaan masyarakat dalam pengelolaan bank sampah - Adam Subarkah; Hadi Cahyono; Sutrisno (Department of Accounting Universitas PGRI Yogyakarta, 2024)
Empowerment is an essential strategy for fostering ecological citizenship. One of the strategies implemented is empowerment to manage and reduce waste accumulation. This research aims to identify strategies to enhance the value of ecological citizenship in waste bank management. This research employs a literature review, conducted by searching various electronic databases to identify literature relevant to the discussion to be presented. The results obtained from this research are as follows: 1) Several approaches are taken to empower waste bank management, known as 5P, including enabling, strengthening, protecting, supporting, and maintaining. 2) The strategy to strengthen ecological citizenship through the Gold Kitiran waste bank community in sustainable waste management is carried out in four stages: environmental knowledge, skills, attitudes, and participation. 3) Obstacles in implementing strategies to strengthen ecological citizenship through waste bank communities in sustainable waste management are divided into internal and external obstacles. These results indicate that community empowerment within waste banks can improve ecological welfare.